Photorealistic simulated modelling from fractals applied to mined-out pit restoration (2014)
3D modelling has been used to simulate the restoration of mining environments, mainly due to ease of use. However, this technique poorly models natural structures, such as leaves, coastlines, mountain systems, etc. Recent digital technology innovations have led to the development of fractal geometry software that reiterates geometric objects at different scales. Below we describe how this geometry can be used for environmental restoration and rehabilitation. We present a case study describing an application of fractal geometry to the restoration of a mined-out open pit. We conclude with a discussion of the advantages — mainly realism and the rapid execution time - of using this type of geometry versus 3D modelling for mining restorations.